2018
DOI: 10.5056/jnm17012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Impaired Motility, and Permeability in a Guinea Pig Model of Postoperative Ileus

Abstract: Background/AimsPostoperative ileus (POI) is characterized by impaired propulsive function of the gastrointestinal tract after surgery. Although inflammation is considered to be an important pathogenesis of POI, significant data are lacking. We aim to correlate the recovery time of postoperative dysmotility with that of inflammation and mucosal permeability. MethodsAn experimental POI model of guinea pig was used. Contractile activity of the circular muscle of the stomach, jejunum, ileum, and proximal colon was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…40,42,43 In line with previous studies, the present study has demonstrated that the population sizes of Bifidobacterium and Lactobacillus decrease in POI groups (Figure 3B,C). Since the inflammatory response and barrier dysfuction have been suggested as the possible main mechanism of POI, 44,45 these findings may aid understanding of the development of POI.…”
Section: Discussionmentioning
confidence: 99%
“…40,42,43 In line with previous studies, the present study has demonstrated that the population sizes of Bifidobacterium and Lactobacillus decrease in POI groups (Figure 3B,C). Since the inflammatory response and barrier dysfuction have been suggested as the possible main mechanism of POI, 44,45 these findings may aid understanding of the development of POI.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 cm portion of the proximal colon was removed and washed in phosphate‐buffered saline (PBS) and then immediately transfer to 4% paraformaldehyde in 0.1 M phosphate buffer (PB, pH 7.4). We selected the proximal colon with the most severe inflammation and decreased contractile activity in the POI state among the peripheral in our previous experiments . Paraffin sections (5 μm) of the whole thickness of the GI segment were processed for immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…We selected the proximal colon with the most severe inflammation and decreased contractile activity in the POI state among the peripheral in our previous experiments. 20 Paraffin sections (5 μm) of the whole thickness of the GI segment were processed for immunohistochemistry. Tissue sections were deparaffinized in xylene for 60 min at 60°C and then rehydrated with 100%, 90%, and 70% alcohol successively.…”
Section: Immunohistochemistry Of Crf In the Proximal Colonmentioning
confidence: 99%
“…That is, the expression of Zonula occludens-1 (ZO-1) and occludin (OCLN) was down-regulated in CRC, but the expressions of claudin (CLDN) 1, 2, 3, and 4 were up-regulated in CRC. 24 In addition, an over expression of protease-activated receptor 2 (PAR-2), which is a family member of G protein-coupled receptors, associated with the increased mucosal permeability in a guinea pig model of postoperative ileus 25 and reflux esophagitis in human. 26 …”
Section: Introductionmentioning
confidence: 99%